Role of Multiple Infections on Immunological Variation in Wild Populations - Ann T. Tate (American Society for Microbiology, 2019)
ABSTRACT A central challenge in the fields of evolutionary immunology and disease ecology is to understand the causes and consequences of natural variation in host susceptibility to infectious diseases. As hosts progress from birth to death in the wild, they are exposed to a wide variety of microorganisms that influence their physical condition, immune system maturation, and susceptibility to concurrent and future infection. Thus, multiple exposures to the same or different microbes can be important environmental drivers of host immunological variation and immune priming. In this perspective, I discuss parasite infracommunity interactions and their imprint on host immunity in space and time. I further consider feedbacks from parasite community dynamics within individual hosts on the transmission of disease at higher levels of biological organization and highlight the promise of systems biology approaches, using flour beetles as an example, for studying the role of multiple infections on immunological variation in wild populations.